The First ASEAN Defence Ministers Meeting: An Early Test for the ASEAN Security Community? - Prawindarti, Lianita (2016)
The 9th of May 2006 is a new landmark in ASEAN's security coorperation as the group's defence ministers held their first-ever meeting in Kuala Lumpur chaired by Malaysian Deputy Prime Minister Datuk Seri Najib Tun Razak. Convening regular ASEAN ministers meetings has become an important element in realising the ASEAN Security Community, specifically its Plan of Action for conflict prevention. This meeting, which will henceforth take place annually.